Wild Phaseolus ecogeography in the Sierra Madre Occidental, Mexico: Aereogeographic techniques for targeting and conserving species diversity - Nebhan, G.P.; International Board for Plant Genetic Resources (1990)
The purpose of this report is to demonstrate more effective strategies for locating and conserving a greater diversity of wild genetic resources related to a given domesticated crop.